Targeted therapies for small cell lung cancer: Where do we stand?. Issue 2 (August 2015) - Arcaro, Alexandre
Highlights SCLC accounts for 15% of all cases of lung cancer and has a dismal prognosis. Several avenues have been explored for targeted therapies in SCLC clinical trials. The PI3K/Akt/mTOR pathway is a promising target to develop new drugs for SCLC.